A new species of Chorisquilla Manning, 1969 (Stomatopoda: Protosquillidae) from Korea and Japan with redescription of C. mehtae Erdmann & Manning, 1998 - Hwang, Hee-Seung; Ahyong, Shane T.; Kim, Won (Zootaxa, 2018)
A new species of protosquillid mantis shrimp is described from the coastal waters of Korea and Japan. Chorisquilla orientalis n. sp. is distinguished from congeners by the combination of deep grooves and pits on the dorsal surface of abdominal somite 5, 8–14 spines on lateral margin of the telson, numerous minute dorsal spines on the telson and abdominal somite 6, and large, pyriform submedian bosses on the telson preceded by a small rounded boss. Chorisquilla orientalis is morphologically closest to C. mehtae Erdmann & Manning, 1998, from Indonesia, but differs chiefly in the dorsal ornamentation of abdominal somite 6 and the telson and reaches a considerably larger size. Chorisquilla orientalis n. sp. shows developmental changes from juvenile to adult in the shape of the ocular scales and anterior margin of lateral plates of carapace, and in the number of lateral spines on telson. Also, C. mehtae Erdmann & Manning, 1998, which, to date has not been adequately illustrated, is redescribed and figured. A key to the Korean gonodactyloids is presented.